Clinical and epidemiological profiles and outcome of non-traumatic myelopathies in dogs - Baka, RD; Balla, S; Kazakos, GM; Patsikas, MN; Polizopoulou, ZS (Journal of the Hellenic Veterinary Medical Society, 2023)
Myelopathies, the disorders affecting the spinal cord, are classified into traumatic or non-traumatic. In dogs, intervertebral disc disease (IVD) is the most common cause of spinal pain and neurological deficits. The aim of the current study is to present the prevalence, clinical presentation, diagnosis and outcome of non-traumatic myelopathies of various etiologies, in dogs. This was a retrospective study in dogs. The inclusion criteria for the dog population included complete clinical records of the cases (physical, neurological examination, clinicopathological and/or diagnostic imaging), therapy, outcome and re-examinations. A total of 618 dogs were included in the study with a mean age of 6 years and a mean body weight of 12Kg. The neurological deficits appeared acutely in 346 dogs (56%).Paraplegia (201/618, 32.5%), paraparesis (144/618, 23.3%) were the most frequent neurological deficits, followed by spinal pain (61/618, 9.9%). In the majority of cases the lesions (374/618, 60.5%) were localized in the thoracolumbar spinal cord segments. Degenerative disc disease was the predominant diagnosis in the study population (212 dogs, 62.5%), followed by neoplasia (10%), congenital anomalies (6.2%), myelitis (5.9%) and, less frequently, discospondylitis (4.1%), caudal cervical spondylomyelopathy (3.8%) and meningitis (3%). There were few cases with extradural synovial cysts (2.1%), congenital myelopathies (1.2%), Chiari like malformation (0.9%). Regarding outcome, 476/618 (77%) dogs were alive at the end of the study. From the 476 dogs that were still alive, 278/476 dogs (58.4%) improved neurologically, 120/476 dogs (25.2%) were neurologically stable, 22/476 dogs (4.6%) deteriorated. Degenerative disc disease was the most common diagnosis in dogs admitted with paraparesis/ paraplegia. Myelography could diagnose secondary spinal compression caused by disc protrusion/ extrusion or any other cause. Corticosteroids and non-steroidal anti-inflammatory drugs (NSAID) were used commonly by the referring veterinarian in case a compressive myelopathy was suspected. Prognosis in dogs with degenerative disc disease type II is favorable when therapy was started soon after the clinical sign’s onset and the deep pain sensation was intact.